The Role of Iraqi TV Satellite Channels in Forming the Attitudes of University Students towards Terror-ism - سبع السنجري, بشرى داود (ALBAHITH ALALAMI, 2018)
The phenomenon of terrorism is one of the most serious challenges facing the world at present. So this concept has occupied a great deal of interest of researchers and scholars in the relevant disciplines. There is no doubt that the study of the concept of terrorism requires a study of its various aspects. However, this study will be limited to knowing the role of television channels in providing the public with information about terrorist events, the extent to which young people rely on these channels to shape their attitudes towards terrorism issues. This study also seeks the relationship between satellite television channels and terrorism based on the relevant media literature such as scientific references and the results of previous studies and research, following the survey method to study the public based on the questionnaire as a research tool distributed to a sample of students from the University of Baghdad's enrolled in the university for 2016. The sample size is 180 students. The research is guided by the theory of dependence to explain changes in public attitudes towards many terrorism issues. In order to achieve the objectives of the research, it is divided into three sections:    the first is the methodological framework of the research, which includes the problem of the research and its questions, the importance of the research and its methodology, and the definition of the concepts and procedures of the previous studies. The second section deals with the theoretical framework which includes the theory of dependence on the media and satellite channels and their relation to terrorism. It includes the results of the field study and the interpretation of tables as well as the general findings and recommendations. The study reaches  several results including the following:1-            Iraqi satellite channels enjoy high visibility when they carry out terrorist operations to be adopted by the public as a source of information in the event of terrorist bombings or emergency events.2-            There are significant differences between males and females in the watch rate, males watch Iraqi satellite channels more than females. The Iraqi channels ranked first among Iraq's favourite channels.3-            E subjects of armed groups through the coverage of Iraqi channels events are reflected in the images of terrorist groups aimed at killing and perpetuating violence in the first order.4-            Accepting the first hypothesis that watching Iraqi satellite channels contributes to the formation of different images of the armed groups in the sample of the research.5-            Do not accept the second hypothesis that the images respondents are about armed groups through the coverage of Iraqi channels of terrorist events according to gender and scientific specialization-human.6-            Accept the third hypothesis that Iraqi satellite channels contribute significantly to the formation of different trends among university youth towards terrorism issues.